TAX COMPLIANCE: THEORIES, RESEARCH DEVELOPMENT AND TAX ENFORCEMENT MODELS - Fauzan Misra (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
Tax compliance is still a serious problem in various countries. This is indicated by the low level of tax compliance and tax ratio. This paper aims to discuss tax compliance from three main perspectives, namely theories about tax compliance, research variables derived from the theory put forward, and models of tax compliance enforcement. Broadly speaking, this theory is divided into two, namely the economic-deterrence model and the fiscal and social psychology model. For a discussion of the research variables that have been tested before, this article follows the classification proposed by Devos (2014). Devos divides these variables into three classifications, namely tax / moral ethics variables, equity and fairness variables and deterrence measures variables. This writing also discusses tax compliance as a behavioral phenomenon. Next, the models of tax law enforcement are explained as proposed by Alm and Torgler (2011) and several other proposed models. Alm and Torgler classified the models into three paradigms, that is, traditional deterrence paradigm, services paradigm, and trust paradigm. These models are proposed to build a mutually beneficial enforcement model for tax authorities and taxpayers.